Piling test / Nurul Nor Hidayah Mat Zain - Mat Zain, Nurul Nor Hidayah (Universiti Teknologi MARA, Perak, 2013)
This report briefly describes the methods and planning, equipment and materials involved in the piling test. It is produced based on the experience of a five-month construction project site located in an apartment building. This report is divided into sections and begins with the background and the background of the construction project. As a result of observations found piling test methods is quite uncomplicated. In construction work under the piling test involves several parties, such as engineers, site supervisors and skilled workers. This report is implemented using several methods of research such as observation, interviews, electronic media and reference materials. In this report, briefly explain the nature and equipment used in the construction. While the construction work is done, there are several problems associated with the piling test process have been identified and the report ended with some suggestions that felt able to solve problems that have been identified. The results of this report have been able to achieve the objectives of piling test process of this building. Finally, the report will explain in more detail the piling test process and method practice to the readers.